Digital Marketing Mix 7P Challenges and Opportunities in Direct-to-Consumer (D2C) Business Models in Indonesia - Betania Kartika Muflih; Abdul Halid Latif (PT Maju Malaqbi Makkarana, 2026)
The rapid growth of Indonesia’s digital economy has accelerated the emergence of Direct-to-Consumer (D2C) business models, enabling firms to establish direct relationships with consumers through proprietary digital platforms. However, the Indonesian D2C ecosystem faces significant structural challenges related to infrastructure fragmentation, platform dependency, consumer heterogeneity, cybersecurity concerns, and digital trust formation. This study examines the challenges and opportunities associated with implementing the Marketing Mix 7P framework within Indonesia’s D2C environment. Using a qualitative literature review approach, this study synthesizes empirical and theoretical findings from digital marketing, e-commerce, omnichannel strategy, and social commerce literature published between 2018 and 2025. The findings indicate that product personalization, first-party data utilization, omnichannel integration, and influencer-driven promotion create substantial opportunities for D2C firms to strengthen customer engagement and competitive advantage. Nevertheless, logistics inequality, high consumer price sensitivity, uneven digital literacy, and marketplace dominance remain critical barriers to sustainable growth. The study further reveals that trust-building mechanisms including secure digital processes, transparent communication, and consistent digital brand representation, function as central determinants of customer loyalty in emerging digital markets. Theoretically, this article extends the contextual application of the Marketing Mix 7P framework by integrating perspectives from relationship marketing, service-dominant logic, and platform economy theory within emerging-market digital ecosystems. Practically, the findings provide strategic insights for digital-native firms operating in highly dynamic and platform-driven markets such as Indonesia.